The Meaning of Interactivity—Some Proposals for Definitions and Measures. (4th May 2017) - Janlert, Lars-Erik; Stolterman, Erik
Abstract : New interactive applications, artifacts, and systems are constantly being added to our environments, and there are some concerns in the human–computer interaction research community that increasing interactivity might not be just to the good. But what is it that is supposed to be increasing, and how could we determine whether it is? To approach these issues in a systematic and analytical fashion, relying less on common intuitions and more on clearly defined concepts and when possible quantifiable properties, we take a renewed look at the notion of interactivity and related concepts. The main contribution of this article is a number of definitions and terms, and the beginning of an attempt to frame the conditions of interaction and interactivity. Based on this framing, we also propose some possible approaches for how interactivity can be measured.